Penerapan Sistem Informasi Akuntansi siklus Pembiayaan Mudharabah sebagai Pengendalian Internal pada BMT Rukun Abadi - Akhirni Putri, Firna Flarestiana; Setiawan, Iwan; Wardiyah, Mia Lasmi (FEB Universitas Sultan Ageng Tirtayasa, 2023)
Mudharabah funding is one of funding product that use collaboration agreement on BMT Rukun Abadi. BMT Rukun Abadi need accounting information system in every transaction, so that the distribution mudharabah funding process can run effectively and efficiently. Accounting information system is one internal control on BMT Rukun Abadi, so that every procedure is done agree with plans for reaching goals that have been set. The application of accounting information system still very simple, it can makes internal control can’t be maximized. The purpose of this research are to know and to analyze: 1) Mudharabah funding procedure on BMT Rukun Abadi. 2) Accounting information system application on BMT Rukun Abadi. 3) Internal control procedure on BMT Rukun Abadi; and 4) Comfirmity accounting information system mudharabah funding cycle with the theory of accounting information system on BMT Rukun Abadi. This research use qualitative research method with descriptive analysis. The data used is primary data obtained from interview result, observasion and documentation, and secondary data obtained from literature riview. The result from this research shows that: 1) Procedure of mudharabah funding has been applicated well on BMT Rukun Abadi. 2) Accounting information system mudharabah funding cycle application on BMT Rukun Abadi already done, but the implementation is still very simple. 3) Internal control procedure on BMT Rukun Abadi has not been implemented optimally; and 4) Accounting information system mudharabah funding cycle on BMT Rukun Abadi already conformity with accounting information system theory.